Correction: RCER: Reliable Cluster-based Energy-aware Routing protocol for heterogeneous Wireless Sensor Networks. - Khalid Haseeb; Naveed Abbas; Muhammad Qaiser Saleem; Osama E Sheta; Khalid Awan; Naveed Islam; Waheed Ur Rehman; Tabinda Salam (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0222009.].